COVID-19 mental health consequences on medical students worldwide. Issue 3 (4th May 2021) - Mittal, Rea; Su, Lilly; Jain, Rohit
ABSTRACT: Background : The COVID-19 epidemic has impacted medical education for medical students worldwide. As medical students are already vulnerable to poor psychological well-being, the mental health of medical students may be significantly affected by the changes caused by COVID-19. Objective : In this article, we discuss the curriculum and mental health ramifications of the COVID-19 epidemic on the international medical school population Methods : In this review, we analyzed 13 studies evaluating the impact of COVID-19 on medical school curriculum, medical student mental health, and subsequent medical student coping strategies. Results : Early in the COVID-19 outbreak, the Association of American Medical Colleges recommended to pause all student clinical rotations, while in-person curriculum moved to virtual modalities. Students expressed concern over their abilities to explore specialties of interest and their confidence in becoming a competent doctor. Medical students also reported higher levels of anxiety, stress, and exhaustion, with female students reporting this more than male students. Students have been coping with these challenges in quarantine through engaging in physical activity, spending time outdoors, and video chats. Conclusion : Medical education institutions must address the effects of COVID-19 on the mental health of their students in order to mitigate related consequences.